2010
DOI: 10.2478/v10042-009-0079-y
|View full text |Cite
|
Sign up to set email alerts
|

The KPC type beta-lactamases: new enzymes that confer resistance to carbapenems in Gram-negative bacilli.

Abstract: Antimicrobial resistance due to the continuous selective pressure from widespread use of antimicrobials in humans, animals and agriculture has been a growing problem for last decades. KPC β-lactamases hydrolyzed β-lactams of all classes. Especially, carbapenem antibiotics are hydrolyzed more efficiency than other β-lactam antibiotics. The KPC enzymes are found most often in Enterobacteriaceae. Recently, these enzymes have been found in isolates of Pseudomonas aeruginosa and Acinetobacter spp. The observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 74 publications
0
29
0
2
Order By: Relevance
“…Since the first report of Klebsiella pneumoniae carbapenemase (KPC) in North Carolina in 2001, bla KPC has spread worldwide (10). In our hospital, bla KPC was found in most Enterobacteriaceae, including K. pneumoniae (2), Escherichia coli (2), Serratia marcescens (22), Enterobacter cloacae (1), and Citrobacter freundii (21).…”
mentioning
confidence: 82%
“…Since the first report of Klebsiella pneumoniae carbapenemase (KPC) in North Carolina in 2001, bla KPC has spread worldwide (10). In our hospital, bla KPC was found in most Enterobacteriaceae, including K. pneumoniae (2), Escherichia coli (2), Serratia marcescens (22), Enterobacter cloacae (1), and Citrobacter freundii (21).…”
mentioning
confidence: 82%
“…Knowing which variant is present might open new treatment options in the future, especially under strict antibiotic stewardship. The difference in resistance profiles and their effects on beta-lactam inhibitors were demonstrated directly in clinical samples and transformants with KPC variants and through comparisons of hydrolytic activities (1,27,28,37,45). Robledo et al (36) reported a variation of antimicrobial susceptibility to carbapenems depending on the KPC variant during a 1-year study based on KPC-producing isolates taken from 6 Puerto Rico Medical Center hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…KPC enzymes hydrolyze at significant levels penicillins, cephalosporins, monobactams and carbapenems, and are weakly inhibited by clavulanic acid and tazobactam (Sacha et al, 2009;Walsh, 2010). Since the first detection of KPC-1/2 in Klebsiella pneumoniae in 2001 in USA, they have been encountered in many other Enterobacteriaceae from the Americas, Europe, Asia and Middle East (Yigit et al, 2001;Nordmann et al, 2009).…”
Section: Sirmentioning
confidence: 99%